Prevalence of asymptomatic submicroscopic malaria in eastern Indonesia: a cross sectional survey and spatial analysis - Jontari Hutagalung, PhD (Elsevier, 2017)
Background: In 2013 in Indonesia, 4·8 million people were infected with malaria, and 23 483 malaria-related deaths were reported. Most infections were reported in eastern Indonesia, with two dominant species of malarial parasite: Plasmodium falciparum(62%) and P vivax (33%). Annual parasite incidence was 15·6 per 1000 population. In 2016, the Indonesian Ministry of Health announced that Indonesia would reach the WHO-defined pre-elimination stage for malaria by 2020, and be free of malaria transmission by 2030. Unfortunately, real data on incidence, surveillance, and mapping of malaria cases is scarce. This study will assess whether East Nusa Tenggara Province in eastern Indonesia should proceed with the malaria pre-elimination stage activities. Methods: We did a survey of 555 people who were systematically selected from five districts in eastern Indonesia. We included healthy participants aged 14 years and older who had a blood haemoglobin concentration ≥100 g/L. We recorded baseline characteristics and risk factors for malaria infection via a standardised questionnaire, and blood samples were taken for analysis. All participants were examined by a local medical doctor. A malaria case was defined as the presence of Plasmodium spp in blood detected with nested PCR (nPCR) or microscopy. Data were collected by standard questionnaire, physical examination and laboratory tests (haemoglobin concentration measurements, microscopic analysis, and nPCR). We mapped nPCR-confirmed cases of malaria using ArcGIS 9.1 spatial and SaTScan analysis. We used univariate and bivariate statistical analysis for statistical analysis. Findings: Between August, 2013, and September, 2014, we included 555 samples in our survey. 181 (32·6%) samples tested positive for malaria with n-PCR: only nine (1·6%) of these cases were detected by microscopy. P vivax was the most common Plasmodium spp detected (94 cases [51·9%]). Not using bednets was the most important risk factors for malaria in our population (OR 2·34, 95% CI 1·98-4·83); fever, which is the most commonly presented symptom, was noted in only five cases (0·9%). Results of spatial analysis showed three distinct and significant clusters: 13 cases (7·2%, p=0·0041), 54 cases (29·9%, p=0·0025), and 87 cases (48·1%, p=0·001). However, all malaria clusters were in areas of low malaria incidence. Interpretation: A malaria pre-elimination programme in eastern Indonesia should be delayed. Routine treatment to stop silent transmission of malaria, and improved laboratory surveillance, are needed. Funding: Asia Pacific Malaria Elimination Network (APMEN) Project number 103-02 as part of the APMEN Country Partner Technical Development Program Round-X. Major funding for APMEN is provided by Australian Government Department of Foreign Affair and Trade, alongside funds received from Bill and Melinda Gates Foundation.